An Insidious Cause of Abdominal Pain in a Preschooler Girl: The Asynchronous Bilateral Ovarian Torsion. Issue 1 (23rd January 2022) - Raffaldi, Irene; Guidi, Carla; Di Gianni, Valeria Rita; Cosentino, Valentina; Personnettaz, Eraldo; Brach del Prever, Adalberto
Abstract: The ovarian torsion (OT) represents one of the most misleading and challenging diagnoses for the pediatrician. Symptoms are often nonspecific, including sudden, piercing localized lower abdominal pain and tenderness associated with a palpable mass and peritoneal signs. Although the adnexal torsion is most frequently unilateral, cases of bilateral synchronous or asynchronous have been recorded; in the latter, the OT involved both ovaries at different settings. We reported the case of a 6-year-old girl who presented an asynchronous bilateral OT.